THE USE OF EMERGENCY SITUATIONS FORECASTING TECHNIQUE AS PART OF A SOFTWARE PLATFORM INTERFACING SYSTEMS OF MONITORING AND EMERGENCY ALERT - V. V. Kopytov; V. V. Naumenko; R. S. Tretiak (Современная наука и инновации, 2022)
The article describes the logical architecture of the integration platform of heterogeneous systems and the use of emergency forecasting techniques in real time mode, which allows to improve the accuracy and reliability offorecasting results for any emergency calculation model, which is intended for use in the framework of situational management software complex.